PEMANFAATAN BIOMASSA LIGNOSELULOSA AMPAS TEBU UNTUK PRODUKSI BIOETANOL - Euis Hermiati; Djumali Mangunwidjaja; Titi Candra Sunarti; Ono Suparno; Bambang Prasetya (Jurnal Penelitian dan Pengembangan Pertanian, 2010)
Utilization of lignocellulosic biomass from sugarcane bagasse for bioethanol production Sugarcane bagasse is one of potential lignocellulosic biomass for energy through physical, chemical or biological conversion. The material is renewable and abundantly available, especially as wastes or by-products of sugarcane industries. Of many conversion processes, lignocellulosic conversion to ethanol becomes focus of interest recently, since ethanol can be further used as biofuel to substitute gasoline for transportation. Lignocellulosic material, including sugarcane bagasse mainly consists of three components, namely cellulose, hemicellulose, and lignin. The conversion of these materials basically consists of pretreatment, cellulose hydrolysis, sugar fermentation to ethanol, and purification of ethanol. Production cost of this conversion is still high; therefore, many researches have been conducted to improve the conversion process, either pretreatment, hydrolysis, fermentation or purification, so that the cost could be reduced. This paper reviewed literatures on potential and characteristics of lignocellulosic materials, especially sugarcane bagasse, and conversion of these materials to ethanol. There is as much as 614,827 kL/year of ethanol potentially produced from sugarcane bagasse resulted from sugarcane factories in Indonesia. This amount of ethanol would have a great contribution to fulfill 1.10 million tons demand of ethanol. However, there are still some recalcitrans in production and implementation of lignocellulosic bioethanol, especially due to the unproven conversion technology of lignocellulosic biomass to ethanol and the high production cost. Therefore, government policies in supporting research and development, providing special incentives for sugarcane factories that produced ethanol from sugarcane bagasse, and giving subsidy to reduce bioethanol price, are needed.Keywords: Sugar by products, lignocellulose, conversion, ethanol